Higher loadings of Pt single atoms and clusters over reducible metal oxides: application to C–O bond activation. Issue 9 (24th March 2022) - Wang, Yunzhu; Lee, Seungyeon; Zhou, Jiahua; Fu, Jiayi; Foucher, Alexandre; Stach, Eric; Ma, Lu; Marinkovic, Nebojsa; Ehrlich, Steven; Zheng, Weiqing; Vlachos, Dionisios G.
Abstract : We develop higher loadings of isolated noble metal atoms and clusters on a metal oxide via redistribution. Abstract : We develop higher loadings of isolated noble metal atoms and clusters on a mildly reducible metal oxide. We demonstrate the approach for Pt supported on TiO2 and confirmed it by XRD, AC-HAADF-STEM, CO-FTIR, XAS, and XPS. Density functional theory calculations rationalize the experimental stability and the IR shifts using mixtures of CH3 I and CO. The redispersed catalysts are thermally stable in inert gas or H2 and afford enhanced selectivity and activity in hydrodeoxygenation reactions compared to metal nanoparticles by creating surface oxygen vacancies that promote C–O cleavage without side reactions. Higher metal loadings, e.g., 1%Pt/TiO2, on the oxide surface profoundly increase the activity of the bare oxide catalyst tenfold compared to ultra-low loadings typically used for single atom catalysis.